White-Sutton syndrome and congenital heart disease: case report and literature review - Jing Duan; Yuanzhen Ye; Jianxiang Liao; Li Chen; Xia Zhao; Chao Liu; Jialun Wen (BMC, 2023)
Abstract Background White-Sutton syndrome is an autosomal dominant neurodevelopmental disorder caused by heterozygous mutation in POGZ (Pogo Transposable Element Derived with ZNF Domain). This syndrome is characterized by delayed psychomotor development apparent in infancy and abnormal facial features. To date, 80 cases have been reported in the literature; however, the phenotypic characterizations remain incomplete. Case presentation We herein describe a 2-year-old girl harboring a novel frameshift de novo POGZ variant: c.2746del (p.Thr916ProfsTer12). This patient presented with multisystem abnormalities affecting the digestive tract and neurological functioning, as well as congenital heart disease, which involved an atrial septal defect (18 × 23 × 22 mm) with pulmonary arterial hypertension (42 mmHg). The relationship between congenital heart disease and White-Sutton syndrome as described in both the GeneReview and OMIM databases (#616,364) remains unclear. A review of the current literature revealed 18 cases of White-Sutton syndrome with POGZ variants and congenital heart disease, and we summarize their clinical features in this study. Conclusions Our findings based on the present case and those in the literature indicate a relationship between POGZ mutation and congenital heart disease.